홈 네트워크와 USN 신호 처리를 위한 u-QoS 지원 네트워크 모듈 개발 - 신재흥(Jae-Heung Shin) (전기학회 논문지 P권, 60(3), 2011)
IPTV functions not only as media player that does play the broadcasting industry's contents, also as the gateway is guaranteed of QoS(Quality of Service). This is for free contents-sharing that device stores contents using home network circumstance, and is for watching with seamless network service. Also this have required next QoS model that can handle stably as it may contain more data of the small computing device in next generation home system. We need ubiquitous-oriented QoS's design and development project that focuses on internal and external media service, not the existing QoS nor one-sided QoS of media sevice industry. This paper focuses on network module development. This supports IPTV in media industry and two-way capability of QoS highlighting multimedia service in network industry. In additional, this can handle stably the multiplex signal of USN/RFID as the representative ubiquitous and home network that services high-speed wire and wireless interface, and support the seamless u-QoS.